2004
DOI: 10.1111/j.0021-9886.2004.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Legitimately Diverse, yet Comparable: On Synthesizing Social Inclusion Performance in the EU*

Abstract: The open method of co-ordination (OMC) intends to enhance EU Member States' performance on social inclusion. In this context a set of commonly agreed performance indicators plays an important role. While the communicative power of a synthetic indicator has been recognized, several objections have been raised against such a construction. In this article, we argue that a set of separate indicators can in principle be combined into a meaningful synthetic performance index without giving up on the notion of subsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 30 publications
(21 reference statements)
2
98
0
6
Order By: Relevance
“…Our original variables come in the form of outputs and inputs. In order to transform all of them into dimensionless outputs, we applied the "distance to the group leader" normalization used by Cherchye et al [73], dividing all output variables by their maximum and dividing the minimum of all input variables by their values. See [12] This program is equivalent to the original DEA formulation, for the case that all variables are outputs.…”
Section: Estimating Quality Of Life Scores In Municipalitiesmentioning
confidence: 99%
“…Our original variables come in the form of outputs and inputs. In order to transform all of them into dimensionless outputs, we applied the "distance to the group leader" normalization used by Cherchye et al [73], dividing all output variables by their maximum and dividing the minimum of all input variables by their values. See [12] This program is equivalent to the original DEA formulation, for the case that all variables are outputs.…”
Section: Estimating Quality Of Life Scores In Municipalitiesmentioning
confidence: 99%
“…Cherchye et al (2004) who firstly implemented this method suggested obtaining the benchmark as solution of a maximisation problem, although external benchmarks are also possible:…”
Section: Benefit Of the Doubt Approach (Bod)mentioning
confidence: 99%
“…Benefit of the doubt (BOD) --e.g., Human Development Index (Mahlberg and Obersteiner, 2001); Sustainable Development (Cherchye and Kuosmanen, 2002); Social Inclusion (Cherchye, Moesen, Van Puyenbroeck, 2004); Macro-economic performance evaluation (Melyn andMoesen, 1991, andCherchye 2001); Unemployment Bjurek, 1999, and.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…Although the DEA domain is very extensive and numerous models exist, making the selection of an appropriate model a rather difficult task, this technique can be translated to be useful for composite indicators. This weighting method has already been used for a number of indexes (Cherchye et al, 2004(Cherchye et al, , 2006Cherchye and Kuosmanen, 2002) and to a limited extent in the road safety context (Odeck, 2005). Its strongest point is that the weights are endogenously determined and derived directly from the data (Cooper et al, 2000).…”
Section: Data Envelopment Analysismentioning
confidence: 99%